Kontekstualisasi PermenLHK No.8/2022 Melalui Literasi Anak Cinta Lingkungan di TBM Pradah Kali Kendal - Zuhda Mila Fitriana; Adelia Savitri; Eka Nanda Ravizki (Fakultas Hukum, UPN Veteran Jawa Timur, 2023)
Nationalism is part of the character that a person has toward his country. Love for the homeland is part of the character that is reflected in a sense of pride, loyalty, concern, and high appreciation for several aspects: language, culture, economy, and politics. In addition, love for the homeland includes practices in protecting the environment such as not littering, considering sustainability in every activity, and trying to reduce carbon production from daily activities. Human negligence as a resident of the earth has brought chronic environmental problems such as climate change. Environmental problems are not only resolved through technical actions but must be supported by awareness and cultivating a loving character for the environment. The real form of fertilizing the character of loving the environment can be through the integration of character education in formal education curricula such as schools. The Indonesian government's latest innovation in involving the younger generation to conserve the environment is regulated in PermenLHK No. 8/2022. This is in line with Weiss's theory of intergenerational justice which emphasizes the obligation of each generation to ensure the environment for the next generation. In addition, this step was taken by the Indonesian government to take advantage of the demographic bonus of the national productive age from 2012 to 2030. Of the many PGL activities, the activities that are most relevant to efforts to cultivate character are the activities of fostering caring behavior and environmental culture. PPPSDM Perkaban No. P.2/P2SDM/SET.11/SDM.2/6/2022 Regarding the Technical Guidelines for the Development of Environmental Generation, it regulates two derivative activities, namely the PBLHS Movement and GEMILANG. One of them is through the development of creativity and innovation of the younger generation to educate the values ​​of loving the environment through digital literacy media. This effort was carried out by the community service team in collaboration with TBM Pradah Kali Kendal.